2011
DOI: 10.1002/jsfa.4557
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, angiotensin‐converting enzyme‐inhibitory activity and antioxidant activities of few‐flower wild rice (Zizania latifolia Turcz.)

Abstract: Both the stem and leaf sheath extracts exhibited good antioxidant properties, while good ACE-inhibitory activity was detected only in the phosphate buffer solution extracts of the stem. Few-flower wild rice could be processed into formula feeds for fish, poultry, etc. or functional foods for persons with high blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The IC 50 value was 2.4 ± 0.1 mg/mL. This inhibition was high compared to that of few-flower wild rice as demonstrated by Qian and colleagues (Qian et al, 2012). Indeed, they have shown that IC 50 value of the stem extracts was approximately 38.54 mg/mL.…”
Section: Resultsmentioning
confidence: 63%
“…The IC 50 value was 2.4 ± 0.1 mg/mL. This inhibition was high compared to that of few-flower wild rice as demonstrated by Qian and colleagues (Qian et al, 2012). Indeed, they have shown that IC 50 value of the stem extracts was approximately 38.54 mg/mL.…”
Section: Resultsmentioning
confidence: 63%
“…Proline and MDA concentrations were measured according to the protocol of Shukla et al [21]. Antioxidant enzyme activity, including SOD, POD, CAT, and GR, were determined following previously reported methods [22], and ascorbic acid and GSH concentration were determined as described in Qian et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of Ca, K, Mg and Na in squid samples were measured using an inductively coupled plasma optical emission spectrometer (OPTIMA-7000DV, Perkin-Elmer, Waltham, MA) according to the method described by Qian et al (2012). The phosphate and chloride concentrations were determined using an 882 ion chromatograph system (Metrohm, Riverview, FL) equipped with a high capacity anion exchange analytical column (Metrosep A Supp 5, 250 mm  4.0 mm).…”
Section: Determination Of Inorganic Ionsmentioning
confidence: 99%